Sleep problems in Korean children with Down syndrome and parental quality of life. Issue 11 (28th July 2019) - Choi, E. K.; Jung, E.; Van Riper, M.; Lee, Y. J.
Abstract: Background: Sleep problems are common among children with Down syndrome (DS), and they can have a serious impact on children with DS as well as their parents and other family members. Specific aims of this study were to evaluate parent‐reported sleep problems in children with DS and to examine the relationship between the sleep behaviour of children with DS and their parents' quality of life (QOL). Method: A cross‐sectional survey was conducted in September and October of 2017. Parents of children with DS were recruited from an online self‐support community for parents of children with DS in South Korea. The mean age of the parents and children with DS was 40.40 years (SD  =  5.09) and 7.89 years (SD  =  3.03), respectively. Children's sleep problems and parents' QOL were assessed using the Children's Sleep Habits Questionnaire and the abbreviated version of the World Health Organization Quality of Life scale, respectively. Results: Results revealed that 83% of the parents reported that their child with DS experienced sleep problems. Children with DS had significantly more bedtime resistance, night waking, parasomnias and sleep‐disordered breathing than did typically developing children. In addition, their Children's Sleep Habits Questionnaire scores were higher than those of typically developing children. Moreover, being older, being male and having more severe developmental delays were significant risk factors for sleep problems among children with DS. Furthermore, sleep problems in children with DS negatively affected parents' QOL. Conclusions: Sleep problems negatively affect children with DS as well as their parents; therefore, health care providers should be aware of these issues and help parents manage sleep problems proactively.